Obstacles to innovation and external sourcing of knowledge: Evidence for German and Spanish firms (2018)
The goal of this research is to empirically study the relationship between obstacles perceived by companies to carrying out their innovation activities and their decisions about external sourcing of knowledge through the outsourcing of R&D or technological cooperation. Using information on German and Spanish companies from the year 2010, we obtain that in both countries this association is positive, and that companies that assign greater importance to factors that impede their innovation activities are also more likely to engage in external sourcing of knowledge. This relationship seems to be especially strong in companies that do not engage in internal R&D activities or do so sporadically, while it is much weaker in companies that perform internal R&D continuously. Nonetheless, the importance that companies assign to the market power of established companies as a barrier to innovation is positively associated with technological cooperation especially in continuous R&D performers.